A hydride generation flow system for determination of arsenic and selenium by total reflection X-ray fluorescence spectrometry - Gomes, ACF; Menegario, A. A.; Pellegrinotti, D. C.; Gine, M. F.; Nascimento, V. F. (Elsevier B.V., 2004)
In this work, a preconcentration and separation system based on continuous flow hydride generation is proposed to improve the determination of As and Se by total reflection X-ray fluorescence spectrometry. The generated hydrides are continuously separated from the liquid phase and collected in a chamber containing 250 mul of HCI/HNO3 1:1 (v/v) solution. Hydride generation conditions and collection of the hydrides were evaluated. Under optimised conditions, enrichment factors of 55 for As and 82 for Se were attained. Detection limits of 0.3 mug l(-1) for As and Se were obtained when 20 ml of sample was used. Analysis of a natural water standard reference material from National Institute of Standard and Technology (SRM-1640) was in agreement with the certified values at the 95% confidence level. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: TXRF; hydride generation; flow system; preconcentration